Experimental Comparison of the Marcus-Hush and Butler-Volmer Descriptions of Electrode Kinetics. The One-Electron Oxidation of 9,10-Diphenylanthracene and One-Electron Reduction of 2-Nitropropane Studied at High-Speed Channel Microband Electrodes - Suwatchara, D; Henstridge, M; Rees, N; Compton, R (2011)
We present an experimental comparative evaluation of the Marcus-Hush (MH) and Butler-Volmer (BV) kinetic formalisms. Numerical simulations using both kinetic models are used to fit experimental voltammetry of the one-electron oxidation of 9,10-diphenylanthracene (DPA) and the one-electron reduction of 2-nitropropane (NP) at a high-speed channel microband electrode. For DPA the Butler-Volmer and Marcus-Hush formalisms yield indistinguishable fits, as expected for a system with fast electrode kinetics. For the BV formalism best fits were obtained using k0 = 0.83 cm s-1 and α = 0.49; for MH the best fit parameters were k0 = 0.85 cm s-1 and λ = 0.58 eV. For NP neither Butler-Volmer nor Marcus-Hush models are able to obtain very accurate fits to experiment, although it was possible for the Butler-Volmer model to yield more accurate fits if the transfer coefficients, α and β, are not required to sum to unity, which is possibly justifiable due to the very large difference between oxidative and reductive peak potentials. The best fit obtained using MH kinetics used k 0 = 7.0 × 10-6 cm s-1 and λ = 1.0 eV, while BV kinetics was able to fit using k0 = 9.5 × 10 -4 cm s-1 and α = β = 0.24. © 2011 American Chemical Society.